2021
DOI: 10.21873/invivo.12507
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Monitoring of Parkinson’s Disease Symptoms With a Wearable Device During COVID-19 Pandemic

Abstract: Background: Accurate assessment of symptoms in Parkinson's disease (PD) is essential for optimal treatment decisions. During the past few years, different monitoring modalities have started to be used in the everyday clinical practice, mainly for the evaluation of motor symptoms. However, monitoring technologies for PD have not yet gained wide acceptance among physicians, patients, and caregivers. The COVID-19 pandemic disrupted the patients' access to healthcare, bringing to the forefront the need for wearabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“… 45 Therefore, providing the feedback of exercise in time is important. In addition, mobile health and virtual reality technology, 52 such as exergaming, 53 social media, 33 wearable technology 54 and robot devices 55 can also be used to improve the exercise experience of PwPDs.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Therefore, providing the feedback of exercise in time is important. In addition, mobile health and virtual reality technology, 52 such as exergaming, 53 social media, 33 wearable technology 54 and robot devices 55 can also be used to improve the exercise experience of PwPDs.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine catalyzed the growth of wearable technologies during the pandemic [62]. Information from wearable technologies could result in quantitative data collection to provide better information about dynamic issues, such as motor and nonmotor fluctuations in Parkinson disease patients [63]. Multiple proof-of-concept studies demonstrated that wearable technologies are helpful tools to optimize patient care [38,63].…”
Section: Disparities In Parkinson Disease Carementioning
confidence: 99%
“…Information from wearable technologies could result in quantitative data collection to provide better information about dynamic issues, such as motor and nonmotor fluctuations in Parkinson disease patients [63]. Multiple proof-of-concept studies demonstrated that wearable technologies are helpful tools to optimize patient care [38,63]. Additionally, development of mobile apps to assess bradykinesia using finger tapping exercises and processing speed may provide a valid measure of bradykinesia [33,38].…”
Section: Disparities In Parkinson Disease Carementioning
confidence: 99%
“…Smart monitoring systems and wearable solutions have emerged during the last two decades to complement the in-person medical assessment [6]. In addition, patients with Parkinson’s disease, caregivers, and healthcare professionals have started using such healthcare practices to overcome barriers in the accessibility toward health units [7]. Besides, the need for objective symptoms’ detection that could effectively direct treatment decisions cannot always be satisfied by clinical evaluation, since this is subjective to physicians’ experience and expertise, and even commonly used rating scales may be susceptible to wide inter- and intra-ratter variability [8].…”
Section: Introductionmentioning
confidence: 99%